The Role of Foundation Grantmakers in Responding to Community Aging: Maine Community Foundation - Jones, Meredith (Maine Policy Review, 2015)
Meredith Jones of the Maine Community Foundation responds to a series of questions about the role of grantmakers in responding to community aging.
Keywords: aging; Maine; grantmakers; philanthropy